Radiological features and internal fixation strategies of atlantoaxial dislocation combined with atlas occipitalization - Liu, Jiang; Jia, Li; Zeng, Minghui; Xu, Hao; Zhao, Shuli; Zhang, Rui; Pang, Qi (European spine journal, 2025)
Background Patients with atlantoaxial dislocation combined with atlas occipitalization often present with variations in the anatomy of the vertebral artery and bone, posing potential risks during the implantation of the C2 pedicle screws during surgery. Objective Based on comprehensive preoperative imaging evaluation, this study investigates the blood supply, course, and relationship with bone of the vertebral artery in patients with atlantoaxial dislocation combined with atlas occipitalization, aiming to provide reference for safe implantation of internal fixation. Methods Imaging data of 77 patients with atlantoaxial dislocation combined with atlas occipitalization from October 2015 to December 2023 at the First Affiliated Hospital of the University of Science and Technology of China were collected, including CT, CT angiography, and MRI. The blood supply, course, and relationship with surrounding structure of the vertebral artery were analyzed using PACS and RadiAnt software. Results There were 18 males and 59 females, with an average age of 48.5 ± 10.5 years (range: 17–71 years). Forty-one cases (53.2%) were associated with congenital C2-3 fusion(Klippel-Feil syndrome). Vertebral artery blood supply was predominantly unilateral (including single blood supply) in 56 cases (72.7%), with left-sided predominance (62.5%). Segment V3 course variations of the vertebral artery were common, with 47 cases (35.6%) not entering the transverse foramen of C1. High-riding vertebral arteries were present in 36 cases (46.8%), with 22 cases (61.1%) associated with congenital C2-3 fusion. The average width of the axis pedicle on the high-riding side was 2.13 ± 1.2 mm, and the height of the isthmus was ≤ 5 mm, with an average of 2.55 ± 1.07 mm. There was a loose gap on the lateral side of the vertebral artery within the transverse foramen, with an average of 2.1 mm, and the corresponding width of the subarachnoid space on the inner side of the axis pedicle was 3.48 mm. Conclusion Comprehensive preoperative imaging evaluation can reduce the risk of vertebral artery injury during surgery in patients with congenital atlantoaxial dislocation combined with atlas occipitalization, and provide feasible and optimized internal fixation solutions.